Modified SVPWM Algorithm for 3-level Inverter Fed DTC Induction Motor Drive - G. Kumara Swamy; YP Obulesu (Institute of Advanced Engineering and Science, 2016)
In this paper, a modified space vector pulse width modulation (MSVPWM) algorithm is developed for 3-level inverter fed direct torque controlled induction motor drive (DTC-IMD). MSVPWM algorithm simplifies conventional space vector pulse width modulation (CSVPWM) algorithm for multilevel inverter(MLI), whose complexity lies in sector/subsector/sub-subsector identification; which will commensurate with number of levels. In the proposed algorithm sectors are identified as in two level inverter and subsectors/sub-subsectors are identified by shifting the original reference vector to sector 1 (S1). This is valid due to the fact that a three level space vector plane is a composition of six two level space planes, and are symmetrical with reference to six pivot states. Switching state/sequence selection is also very important while dealing with SVPWM strategy for MLI. In the proposed algorithm out of 27 available switching states apt switching state is selected based on sector and subsector number, such that voltage ripple is considerably less. To validate the proposed algorithm, it is tested on a three level neutral point clamped (NPC) inverter fed DTC-IMD. The performance of the MSVPWM algorithm is analyzed by comparing no load stator current ripple of the three level DTC-IMD with two level DTC-IMD. Significant reduction in steady state torque and flux ripple is observed. Hence, reduced acoustic noise is a distinctive facet of the proposed method.